Policy Tools for Urban Redevelopment: Public-Private Partnerships - Roger E. HAMLIN; Bogdana NEAMŢU (Transylvanian Review of Administrative Sciences, 2005)
This paper addresses the issue of inner city redevelopment and focuses on possible policy tools that may be used to cope with declining urban areas (for e.g., the public-private partnership). This paper has a twofold structure. Within the first part it will review some of the existing literature on this topic so as to develop a theoretical framework for understanding urban redevelopment within the American cities. The second part emphasizes the importance of public-private partnerships for inner city redevelopment consists in a case study about an inner city redevelopment. It also addresses some of the limitations associated with such partnerships and how they can be mitigated. In the conclusion section it is argued that declining urban areas and the need for innovative strategies to cope with these issues are to be found also within the European cities. Even though European downtowns have remained a desirable place to live, aging industrial cities are definitely a serious problem that needs to be dealt with by policy makers. Accordingly, the point we try to make is that urban decline is a serious challenge for both American and European local governments and, with modification, some of the same tools can be used.